A Cryogenic Interface for Controlling Many Qubits - Pauka, S. J.; Das, K.; Kalra, R.; Moini, A.; Yang, Y.; Trainer, M.; Bousquet, Arnaud; Cantaloube, C.; Dick, N.; Gardner, Geoff; Manfra, M. J.; Reilly, David (2019)
A scaled-up quantum computer will require a highly efficient control interface that autonomously manipulates and reads out large numbers of qubits, which for solid-state implementations are usually held at millikelvin (mK) temperatures. Advanced CMOS technology, tightly integrated with the quantum system, would be ideal for implementing such a control interface but is generally discounted on the basis of its power dissipation that leads to heating of the fragile qubits. Here, we demonstrate an ultra low power, CMOS-based quantum control platform that takes digital commands as input and generates many parallel qubit control signals. Realized using 100,000 transistors operating near 100 mK, our platform alleviates the need for separate control lines to every qubit by exploiting the low leakage of transistors at cryogenic temperatures to store charge on floating gate structures that are used to tune-up quantum devices. This charge can then be rapidly shuffled between on-chip capacitors to generate the fast voltage pulses required for dynamic qubit control. We benchmark this architecture on a quantum dot test device, showing that the control of thousands of gate electrodes is feasible within the cooling power of commercially available dilution refrigerators.